Cerebral Toxoplasmosis in a patient with Pneumocystis: a case report - Nogueira, João Vítor Moreira; Rocha, Luana Cariello de Sá Queiroz; Albuquerque, Letícia Rocha Macambira; Oliveira, Athos Hiago da Silva; Cefali, Felipe Bergamasco Perri; Silva, Nathalia Alves da; Viana, Tayenne Nélly de Lucena; Madeira Neto, Rodolfo Basílio; Alves, Desirée Louise Procópio; Alencar, Felipe Rios Moraes Andrade de; Carvalho, Anderson Arthur Marques de; Gonçalves, Maria Carolina Marinho de Andrade; et al. (Brazilian Journal of Case Reports, 2023)
Acquired Immune Deficiency Syndrome, or AIDS, is characterized by a clinical condition in which the body’s defenses suffer a gradual depletion, making it susceptible to a wide variety of infections. Among these, neurotoxoplasmosis is a characteristic opportunistic infection caused by Toxoplasma gondii. This infection generates numerous neurological deficits that can regress if early diagnosis and intervention are carried out. However, underdiagnosis of these cases due to incorrect management or inaccurate diagnosis leads to damaging and permanent results due to the expansive nature of the mass, which affects a wide range of organic functions. It is then associated with infection by Pneumocystis jirovecii, also characteristic of immunodeficient patients, demonstrating a synergism between the mechanisms that facilitate the infectious process. Because of the seriousness of these infections and their association, a clinical picture like this must be well visualized.